Penyusunan Standar Asuhan Keperawatan Dan Panduan Asuhan Keperawatan Sebagai Standar Penerapan Asuhan Keperawatan Berbasis SDKI, SLKI Dan SIKI Di Rumkit TK. II Prof. Dr. J.A. Latumeten Ambon. - Ireine Tauran; Hasna Tunny (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
The Nursing Care Guide (PAK) is a very important resource for the nursing profession in implementing nursing care, because nurses are a profession that performs nursing care for patients 24 hours a day. PPNI as the official organization of nurses has established SDKI, SLKI and SIKI as standards in providing nursing care. The purpose of this activity is to provide SAK and PAK based on SDKI, SLKI and SIKI. The method used is lectures and discussions, lectures related to the problems found and discussions related to the preparation of SAK and PAK. Participants numbered 20 people consisting of nursing students and heads of rooms. As a result of the activity, SAK and PAK were arranged which consisted of 13 medical diagnoses and 28 nursing diagnoses.